The Mechanism of Calcium Handling Proteins and NF-κB in Calcium Dyshomeostasis of Cardiomyocytes Caused by Acute MDMA Exposure - WANG Rong-shuai; HUANG Si-zhe; WANG Yun-yun; DENG Yan-fei; DING Zi-jiao; ZHANG Jie; LIU Yong; REN Liang; LIU Liang (Fayixue Zazhi)
ObjectiveTo explore the mechanism of myocardial toxicity caused by N-methyl-3,4-methyle-nedioxyamphetamine （MDMA）, the changes of intracellular calcium oscillation mode and calcium handling proteins during acute exposure to different concentrations of MDMA were detected, and the involvement of nuclear factor κB （NF-κB） and its effect on calcium handling proteins were investigated.MethodsPrimary rat cardiomyocytes were cultured to establish MDMA acute exposure model, and a control group was set up. The MDMA poisoning model was divided into three concentration groups of 10, 100 and 1 000 μmol/L. After 1 h of exposure, the morphological changes of cardiomyocytes were observed, the cytotoxicity and changes in calcium signals were measured, and the changes in calcium handling proteins RyR2, SERCA2a, PLN, NCX1 and Cav1.2 were detected. The changes of NF-κB activity and the expression of nucleoprotein p-p65 （Ser311） and PKCζ after MDMA exposure, and the intervention of NF-κB inhibitors pyrrolidine dithiocarbamate ammonium （PDTC） and protein kinase C （PKC） inhibitor chelerythrine （CHE） were detected by electrophoretic mobility shift assay （EMSA） and Western blotting. The effects of PDTC intervention on calcium signals, and the expressions of RyR2, SERCA2a, PLN, NCX1 and Cav1.2 after acute MDMA exposure were also observed.ResultsNo obvious changes were observed in the morphology of cardiomyocytes after acute exposure to MDMA, whereas the oscillation waveform of intracytoplasmic calcium ion showed irregular changes with increased oscillation amplitude, intense fluctuations, irregular frequency, and increased fluctuation range of relative optical density values. The expression of RyR2, SERCA2a and NCX1 increased, while the expression of Cav1.2 and PLN decreased. Acute MDMA exposure could increase NF-κB activity, while PDTC and CHE intervention could inhibit NF-κB activity. In MDMA exposed group, the expression of PKCζ and nucleoprotein p-p65 （Ser311） both increased and could be inhibited by CHE. After the intervention of PDTC to block NF-κB, the amplitude of calcium oscillation was lower than that of the MDMA exposed group, and the expression of RyR2, SERCA2a and NCX1 decreased. There was no significant change in PLN, while the expression of Cav1.2 increased.ConclusionMDMA can lead to an increase of calcium ion concentration in cardiomyocytes. Calcium ions are involved in myocardial toxicity of MDMA. The mechanism is related to changes in calcium handling proteins, mainly associated with the increased expression of RyR2. MDMA can up-regulate the intracellular activity of NF-κB through the PKCζ-NF-κB pathway and affect calcium handling proteins, which aggravate intracellular calcium overload during acute MDMA exposure.